Prediction of Pore Volume Dispersion and Microstructural Characteristics of Concrete Using Image Processing Technique - Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Concrete has served an essential role in many infrastructural projects. Factors including pore percentage, pore distribution, and cracking affect concrete durability. This research aims to better understand pore size distribution in cement-based materials. Micro-computed tomography (micro-CT) pictures were utilised to characterise the interior structure of specimens without destroying them. The pore dispersion of the specimens was displayed in 3D, utilising the data and imaging techniques collected, and the pore volume dispersion was examined using a volume-based approach. Another way to describe heterogeneous pore features is the chord-length distribution, which was calculated from three-dimensional micro-CT scans and correlated with the traditional method. The collected specimens were subjected to physical and mechanical testing. In addition, image processing techniques were used to conduct the studies. The results showed that the chord-length distribution-based pore size distribution is very successful than the traditional volume-based technique. The acquired data could be used for research and to forecast the characteristics of the materials. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).